UPAYA MELENGKAPI SARANA DAN PRASARANA PENDIDIKAN MADRASAH - Triyono, Agus (El-Hamra, 2019)
One aspect that must get attention in managing education is about the infrastructure needed. Educational facilities are equipment that includes all facilities that are directly used and support the process of implementing education services. Whereas what is meant by facilities / infrastructure is that which indirectly supports the course of the education process. Educational services cannot be separated from the availability of facilities and infrastructure, because allservice components definitely need it. Therefore the madrasa as much as possible to organize and prepare needs that are very influential on these education services. Schools with complete facilitie and infrastructures will be able to do better services compared to madrassas with incomplete facilities.Key Words: Facilities and infrastructure, madrasa education